Beating Burnout in Congregations - Baab, Lynne M. (Rowman & Littlefield Publishers, 2003)
I can only shake my head in the face of the irony that all too often the very place where we look for life and health, the very place where we expect to nurture and deepen a loving relationship with God, can cause so many to experience the exact opposite. So remarks author Lynne Baab in this timely and discerning examination of burnout in congregations. What is burnout? What causes congregation volunteers to burn out? Why is unpaid service sometimes life giving and other times just another frantic commitment? How can congregations become oases of peace and nurture while still carrying out their mission and ministry? How can we recognize holy moments in the presence of God if we are moving so fast that life passes by us in a blur? How can leaders make congregations healthy places to serve? After reflecting on these important questions and dozens of interviews with congregation volunteers, Baab suggests, "We must not fear burnout; instead, we need to do a better job coming alongside people as they experience burnout, and help them figure out what they are learning."